2021
DOI: 10.3390/antibiotics10020162
|View full text |Cite
|
Sign up to set email alerts
|

Sulfaguanidine Hybrid with Some New Pyridine-2-One Derivatives: Design, Synthesis, and Antimicrobial Activity against Multidrug-Resistant Bacteria as Dual DNA Gyrase and DHFR Inhibitors

Abstract: Herein, a series of novel hybrid sulfaguanidine moieties, bearing 2-cyanoacrylamide 2a–d, pyridine-2-one 3–10, and 2-imino-2H-chromene-3-carboxamide 11, 12 derivatives, were synthesized, and their structure confirmed by spectral data and elemental analysis. All the synthesized compounds showed moderate to good antimicrobial activity against eight pathogens. The most promising six derivatives, 2a, 2b, 2d, 3a, 8, and 11, revealed to be best in inhibiting bacterial and fungal growth, thus showing bactericidal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 75 publications
1
22
0
Order By: Relevance
“…All compounds showed excellent antibacterial activity against the tested bacterial strains S. aureus , E. faecalis , E. coli , A. baumannii , and P. aeruginosa with MIC concentrations of 31.25 to 62.5 μg mL −1 . Ragab et al [ 22 ] reported the synthesis of pyridine compounds 36 (by ternary condensation of cyanoacetamide 35 , aromatic aldehyde and malononitrile in an equimolar molar ratio 1:1:1 in basic ethanol) and 37 (by cyclo-condensation of cyanoacetamide 35 with acetylacetone in DMF) with very good antimicrobial activity against all tested strains B. subtilis , S. aureus , E. faecalis , E. coli , P. aeruginosa , S. typhi , C. albicans, and F. oxysporum (MIC = 18–31 μM) ( Table 1 ).…”
Section: Synthesis Of Antimicrobial Compounds Containing Only Pyridin...mentioning
confidence: 99%
“…All compounds showed excellent antibacterial activity against the tested bacterial strains S. aureus , E. faecalis , E. coli , A. baumannii , and P. aeruginosa with MIC concentrations of 31.25 to 62.5 μg mL −1 . Ragab et al [ 22 ] reported the synthesis of pyridine compounds 36 (by ternary condensation of cyanoacetamide 35 , aromatic aldehyde and malononitrile in an equimolar molar ratio 1:1:1 in basic ethanol) and 37 (by cyclo-condensation of cyanoacetamide 35 with acetylacetone in DMF) with very good antimicrobial activity against all tested strains B. subtilis , S. aureus , E. faecalis , E. coli , P. aeruginosa , S. typhi , C. albicans, and F. oxysporum (MIC = 18–31 μM) ( Table 1 ).…”
Section: Synthesis Of Antimicrobial Compounds Containing Only Pyridin...mentioning
confidence: 99%
“…Molecular docking was performed using Molecular Operating Environmental (MOE) software version 2008.10. [68][69][70] The designed ligand and its complexes exhibited binding energy ranged from À16.96 to À20.16 Kcal mol À1 . The phenyl and furan rings developed hydrophobic interactions with DNA base pair for all synthesized derivatives.…”
Section: Molecular Docking Studymentioning
confidence: 99%
“…The generation of active sites was achieved according to the previously reported literature. [80] The theoretical binding mode achieved between the active site of DNA gyrase and pyrazole derivatives is presented in Table 5 and group with bond lengths of 2.72 Å (12%) and 2.59 Å (80%), respectively. Besides, one hydrogen-bond side-chain donor was present between the phenolic hydroxy group (OH) and the amino acid Glu435 in the active site with bond length 2.33 Å and strength 43% (Figure 6c,d).…”
Section: Dna Gyrase Inhibitory Assaymentioning
confidence: 99%
“…A molecular docking study for the most active derivatives inside the active site of the DNA gyrase (PDB: 2XCT) enzyme assay was performed according to the reported method [80] using the Molecular Operating Environment docking tool 10.2008 (MOE). Simultaneously, the DFT calculation and MEP were obtained through Gaussian 09 software after optimizing the synthesized derivatives with DFT calculations using the B3LYP hybrid functional and standard 6-31G(d) basis set according to the reported method.…”
Section: Computational Studymentioning
confidence: 99%